The pathophysiological impact of stress on the dopamine system is dependent on the state of the critical period of vulnerability - Gomes, Felipe V. (Mol Psychiatry, 2019)
Unregulated stress during critical periods of development is proposed to drive deficits consistent with schizophrenia in adults. If accurate, reopening the critical period could make the adult susceptible to pathology. We evaluated the impact of early adolescent and adult stress exposure (combination of daily footshock for 10 days and 3 restraint sessions) on 1) midbrain dopamine (DA) neuron activity, 2) ventral hippocampal (vHipp) pyramidal neuron activity, and 3) the number of parvalbumin (PV) interneurons in the vHipp and their associated perineuronal nets (PNNs). Ventral tegmental area (VTA) DA neuron population activity and vHipp activity was increased 1–2 and 5–6 weeks post-adolescent stress, along with a decrease in the number of PV+, PNN+, PV+/PNN+ cells in the vHipp, which are consistent with the MAM model of schizophrenia. In contrast, adult stress decreased VTA DA neuron population activity only at 1–2 weeks post-stress, which is consistent with what has been observed in animal models of depression, without impacting vHipp activity and PV/PNN expression. Administration of valproate (VPA), which can re-instate the critical period of plasticity via histone deacetylase (HDAC) inhibition, caused adult stress to produce changes similar to those induced by adolescent stress, presumably by increasing stress vulnerability to early adolescent levels. Our findings indicate that timing of stress is a critical determinant of the pathology produced in the adult: adolescent stress led to circuit deficits that recapitulates schizophrenia, whereas adult stress induced a depression-like hypodopaminergic state. Reopening the critical period in the adult restores vulnerability to stress-induced pathology resembling schizophrenia.